Theory of Change in complex Research for Development programmes: chall enges and solutions from the Global Challenges Research Fund - Chapman, Sarah; Boodhoo, Adiilah; Duffy, Carren; Goodman, Suki; Michalopoulou, Maria (The European Journal of Development Research, 2023)
The United Kingdom Research and Innovation (UKRI) Global Challenges Re search Fund (GCRF) aimed to address global challenges to achieve the U nited Nations (UN) Sustainable Development Goals through 12 interdisci plinary research hubs. This research documents key lessons learned aro und working with Theory of Change (ToC) to guide Monitoring, Evaluatio n and Learning (MEL) within these complex research for development hub s. Interviews and document reviews were conducted in ten of the resear ch hubs. The results revealed that only one hub invested in an explici t visual system mapping approach, and that funder timelines, budget co nstraints and issues with capacity and expertise limited the applicati on of these approaches across all hubs. In contrast, many hubs attempt ed to deal with visual complexity by means of ether constructing multi ple, nested ToCs, or a conscious simplification of complexity through reducing their ToC towards a straightforward and uncomplicated chain m odel or spherical model. While the former approach had some value, mos t hubs struggled to find capacity to support the full articulation of nested ToCs. In contrast, the latter approach resulted in ToCs which l acked detail or mechanism articulation, but which nevertheless were of ten ‘fit for purpose’ in ensuring effective communication and coherenc e across diverse stakeholders and sub-projects. We conclude that in in stances where the reporting, funding and management cycles of complex research for development programmes cannot be adapted to properly supp ort learning-based approaches to ToC development, imposing simplicity in the ToC might be fit for purpose. This might also be preferable to more complex visual approaches that are only partially realised.